EPISTEMOLOGI ISLAM DAN REKONSTRUKSI PARADIGMA ILMU DI ERA MODERN - Enden Siti Nur Fathonah; Ani Rindiani; Cucu Siti Rabi'ah; Ririt Komariah (Program Studi Pendidikan Guru Sekolah Dasar FKIP Universitas Pasundan, 2025)
This study aims to provide a brief explanation of the important points in the study of Islamic epistemology, particularly its characteristics that unite revelation and reason, as well as its role in the process of Islamization of science and in facing the crisis of knowledge in modern times. This study uses a qualitative method with a literature study approach, and the data is analyzed descriptively. The results of the study indicate that Islamic epistemology is a perspective that combines revelation, reason, intuition, and experience as complementary sources of knowledge. Based on the belief in the oneness of Allah (tauhid), this system emphasizes not only logic and experience but also spiritual values and ethics. The primary purpose of knowledge in Islam is to draw closer to Allah, understand the meaning of life, and build a moral civilization. With the support of classical and modern Islamic thinkers, Islamic epistemology serves as a crucial foundation for reimagining the secular perspective of modern science. In the context of the current crisis of values and knowledge, Islamic epistemology offers a solution that unites science and values for the benefit of humanity and the will of God.